Inverted classroom improves pre-university students understanding on basic topic of physics: the preliminary study - Elnetthra Folly Eldy; Jackson Chang Hian Wui; Siti Nazirah Butai; Nur Fadzilah Basri; Huzaikha Awang; Wardatul Akmam Din; Sazmal Effendi Arshad (Journal of Technology and Science Education, 2019)
This paper discusses the effectiveness of the inverted classroom implemented in a pre-university physics classroom on topics of classical mechanics. Inverted classroom moves from traditional lectures to providing students with pre-recorded lectures and other materials such as videos, online quizzes and online exercises to foster independent learning. In this study, the classroom was divided into two groups: a control group and experimental group intervened with the inverted classroom; in evaluating the efficiency of the intervention, at the end of the module, both groups were tested using tests that are similar. The findings show that there was a significant difference between control group and experimental group on their pre-test and post-test score. It implies the potential use of this approach in other basic topics of pre-university physics classroom.